Assessment of beddown alternatives for the F-35 : executive summary - McGarvey, Ronald G.; Bigelow, J. H.; Briggs, Gary; Buryk, Peter; Conley, Raymond E.; Drew, John G., 1956-; Firoz, Perry Shameem; Kim, Julie; Menthe, Lance; Moore, S. Craig, 1946-; Taylor, William W., 1938-; Williams, William A., 1952- (RAND, 2013)
As currently planned, the F-35 Joint Strike Fighter is the most costly aircraft acquisition program in Defense Department history. One approach to ensuring program affordability could be to increase the number of Primary Aerospace Vehicles Authorized (PAA) per combat-coded squadron, with a resulting reduction in the number of F-35 combat-coded squadrons. RAND explored the impact of increasing the PAA per squadron, adjusting the mix of PAA across the Active and Reserve Components, and adjusting the percentage of the Active Component PAA assigned to home-station locations in the continental United States. Researchers considered 28 beddown alternatives, with a maximum of 36 PAA per squadron, and determined that all beddowns could satisfy surge deployment requirements and most could also satisfy rotational requirements within specified deploy-to-dwell ratios. Increasing squadron size was determined to significantly reduce (a) the flying costs necessary to achieve pilot absorption requirements, (b) maintenance manpower requirements, and (c) total support equipment procurement costs, while little additional infrastructure capacity would be required under any of the 28 basing alternatives considered. Additional analysis suggested that assignment policy would have more effect on leader development than either squadron size or the active-reserve mix.